Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Kekerasan (Child Abuse) di Indonesia - I Gusti Ngurah Agung Bija Karang; I Nyoman Gede Sugiartha; Luh Putu Suryani (Jurnal Analogi Hukum, 2021)
Violence against children that occurs in Indonesia a lot occurs because of the lack of awareness of parents or child caretakers towards the protection of children. Violence that often occurs includes physical, emotional, sexual and neglect of children, which is included in the violence of the criminal act of child abuse. The need for the application of a legal basis for acts of violence against children child abuse in Indonesia to prevent the development of such cases. So with that, the formulation of the problem in this study is how the legal arrangements for perpetrators of criminal acts of violence against child abuse in Indonesia are and how is the process of criminal sanctions against perpetrators of child abuse. The research methodology used is normative law. The results of this study describe that acts of child abuse in Indonesia can be protected through the legal basis of Law Number 35 of 2014 concerning Child Protection which has criminal sanctions on the perpetrators which are regulated in Article 80.